Sobre Verbascum × longiracemosum Chaub. ex St.-Amans (Scrophulariaceae) en la comunidad valenciana. Verbascum × longiracemosum Chaub. ex St.-Amans (Scrophulariaceae) from Valencian Community - Oltra Benavent, Josep E.; Ferrer-Gallego, P. Pablo (Acta Botanica Malacitana, 2012)
Verbascum × longiracemosum Chaub. ex St.-Amans (Scrophulariaceae) from Valencian Community Palabras clave. Verbascum × longiracemosum, Scrophulariaceae, híbrido, Valencia, España. Key words. Verbascum × longiracemosum, Scrophulariaceae, hybrid, Valencian province, Spain.